An Empirical Analysis of Financial Ratios and Financial Performance among Telecommunication Companies Listed on the Indonesia Stock Exchange, 2022–2024 - Ghina Salsabila; Lalu Hamdani Husnan (Economics and Business Journal (ECBIS), 2026)
The rapid growth of the telecommunications industry, driven by increasing demand for digital services, is not always accompanied by stable financial performance due to cost pressures, competition, and infrastructure investment requirements. This condition requires companies to manage their finances effectively, making financial ratio analysis important in evaluating corporation performance. This study aims to analyze the effect of activity ratios, liquidity ratios, and solvency ratios on the financial performance of telecommunication companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research uses a quantitative approach with a descriptive research design. The data used are secondary data obtained from financial statements. The sampling technique uses purposive sampling with 18 companies over a three-year period, resulting in 54 observations. The analysis method used is multiple linear regression with SPSS. The independent variables include activity ratio (TATO), liquidity ratio (CR), and solvency ratio (DER), while the dependent variable is financial performance (ROE). The outcome show that partially, the activity ratio does not have a substantial effect on financial performance. Meanwhile, liquidity and solvency ratios have a negative and substantial effect on financial performance. Simultaneously, all three ratios have a substantial effect on financial performance. These findings indicate that financial performance is influenced by asset management, the ability to meet obligations, and capital structure.